Feasibility of Urgent-Start Peritoneal Dialysis in Older Patients with End-Stage Renal Disease: A Single-Center Experience. Issue 2 (March 2018) - Jin, Haijiao; Ni, Zhaohui; Mou, Shan; Lu, Renhua; Fang, Wei; Huang, Jiaying; Hu, Chunhua; Zhang, Haifen; Yan, Hao; Li, Zhenyuan; Yu, Zanzhe
Background: Patients with end-stage renal disease (ESRD) frequently require urgent-start dialysis. Recent evidence suggests that peritoneal dialysis (PD) might be a feasible alternative to hemodialysis (HD) in these patients, including in older patients. Methods: This retrospective study enrolled patients aged > 65 years with ESRD who underwent urgent dialysis without functional vascular access or PD catheter at a single center, from January 2011 to December 2014. Patients were grouped based on their dialysis modality (PD or HD). Patients unable to tolerate PD catheter insertion or wait for PD were excluded. Each patient was followed for at least 30 days after catheter insertion. Short-term (30-day) dialysis-related complications and patient survival were compared between the 2 groups. Results: A total of 94 patients were enrolled, including 53 (56.4%) who underwent PD. The incidence of dialysis-related complications during the first 30 days was significantly lower in PD compared with HD patients (3 [5.7%] vs 10 [24.4%], p = 0.009). Logistic regression identified urgent-start HD as an independent risk factor for dialysis-related complications compared with urgent-start PD (odds ratio 4.760 [1.183 – 19.147], p = 0.028). The 6-, 12-, 24-, and 36-month survival rates in the PD and HD groups were 92.3% vs 94.6%, 82.4% vs 81.3%, 75.7% vs 74.2%, and 69.5% vs 60.6%, respectively, with no significant differences between the groups (log-rank = 0.011, p = 0.915). Conclusion: Urgent-start PD was associated with fewer short-term dialysis-related complications and similar survival to urgent-start HD in older patients with ESRD. Peritoneal dialysis may thus be a safe and effective dialysis modality for older ESRD patients requiring urgent dialysis.